Psychological Safety dalam Setting kerja hibrid: Analisis Studi Kasus Multi-Situs pada Perusahaan Multinasional X - Mulyadaning, Agriana; Kunaif , Aang (Universitas Muhammadiyah Pontianak, 2026)
This multi-site qualitative study explores psychological safety in PT Multinational X’s hybrid work setting across Jakarta, Bandung, and Surabaya. Through interviews and document analysis, it reveals varied experiences shaped by local contexts. Key enablers include proactive leadership, clear communication, and transparent policies, yet implementation demands contextual adaptation. Challenges such as weakened informal communication and proximity bias are intensified by regional issues like Surabaya’s digital divide and Bandung’s perfectionist culture. The study recommends a dual-layered strategy standardizing core principles while allowing local flexibility to foster psychologically safe environments across diverse office settings.